PERSPEKTIF AL-QURAN DAN INJIL TENTANG KECERDASAN NATURALIS - Febriani, Nur Arfiyah (Direktorat Jenderal Bimbingan Masyarakat Islam, 2017)
Naturalist intelligence carried by Holy Quran and Injil synergizes human spiritual dimention for the God as the center. With the faith to the God and His teaching the human hope to be able to reconstruct the anthropocentric paradigm and finally it can influence the interaction pattern in harmony with the environment (Max Weber, 197). Naturalist intelligence can be understood in the meaning, the people ability in understanding and loving the environment by taking care its sustainability as the responsibility and worship for the God (read Allah SWT in Holy Quran), as the individual creatures, social, and spiritual (Febriani, 2013). Kecerdasan naturalis yang diusung kitab al-Quran dan Injil mensinergikan dimensi spiritual manusia kepada Tuhan sebagai centernya. Dengan ketaatan pada Tuhan dan ajaran-ajaran-Nya manusia diharapkan dapat merekonstruksi paradigma antroposentris yang pada akhirnya dapat mempengaruhi pola interaksi yang harmonis dengan lingkungan (Max Weber, 1978). Kecerdasan naturalis dapat dipahami dalam arti, kemampuan seseorang dalam memahami dan mencintai lingkungan dengan senantiasa menjaga kelestariannya sebagai bentuk tanggung jawab dan ibadah kepada Tuhan (baca: Allah SWT dalam al-Quran), baik sebagai makhluk individu, sosial dan spiritual (Febriani, 2013).